PWE-210 Needle-based confocal laser endomicrosocpy for pancreatic cystic lesions: initial results from the UK concyst study. (22nd June 2015) - Keane, MG; Stefanescu, D; Cieplik, N; Fusai, GK; Thorburn, D; Metz, A; Pereira, SP
Abstract : Introduction: Pancreatic cystic lesions (PCL) are an increasingly common clinical finding, present in up to 2% of patients undergoing CT and 14% of those undergoing MRI for non-pancreatic indications. Cytology from endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) often has a low diagnostic yield. Needle-based confocal laser endomicroscopy (nCLE) allows a sub-millimetre AQ-flex 19 miniprobe (Mauna Kea Technologies, Paris, France) to be inserted into the cyst via a 19G FNA needle, enabling real-time imaging of the interior of the cyst. The aim of the study was therefore to evaluate the diagnostic potential, safety and efficacy of nCLE in the management of indeterminate PCL. Method: The CONCYST study aims to recruit 60 patients prospectively with indeterminate CLP who require EUS-FNA from hepatopancreaticobiliary referral centres with nCLE in the UK; currently Royal Free Hospital, London, and Addenbrooke's Hospital, Cambridge. The study commenced in July 2014; 21 patients have been recruited to date. The procedure was performed under conscious sedation (Midazolam and Fentanyl). Patients received antibiotics immediately prior to the start of the procedure. 2.5mls of 10% fluorescein was injected once the cyst was visualised at EUS. After observation in the recovery room for up to 4 h all patients were discharged home the same day. Following the procedure all patients were followed up by telephone clinic. Ethical approval for the study was granted by the National Research Ethics Service (14/LO/0040). Results: Of the 21 patients that underwent EUS-nCLE, 12 were male and 9 female. Median age was 70 (range 40–86) years. Confocal images were obtained in all cases. Median nCLE scanning time was 5 min and did not exceed 10 min in any case. EUS-nCLE findings correlated with final diagnosis (based on imaging, cytology and multidisciplinary team review) in 91% (19/21) of cases which was superior to cytology alone which correlated with final diagnosis in 71% (15/21) of cases. One patient experienced mild pruritus immediately following the procedure (possibly related to the fluorescein injection) but this settled promptly with a single dose of chlorphenamine. No complications were reported during follow-up. Conclusion: These preliminary results are encouraging and suggest that nCLE under conscious sedation in the daycase setting is safe. Our initial findings indicate that EUS-nCLE is more sensitive than standard EUS-FNA for diagnosing indeterminate cystic lesion of the pancreas, but larger numbers will be required to confirm these findings. Disclosure of interest: None Declared.